Improvement in the photovoltaic efficiency of polymer solar cells by treating the poly(3,4-ethylenedioxythiophene): Poly(styrenesulfonate) buffer layer with co-solvents of hydrophilic organic solvents and hydrophobic 1,2-dichlorobenzene - Sun, K. (2014)
10.1016/j.solmat.2011.09.039